PENGARUH KARAKTERISTIK INDIVIDU, KARAKTERISTIK PEKERJAAN, LINGKUNGAN KERJA TERHADAP STRES KERJA KARYAWAN ADMINISTARSI UMUM RUMAH SAKIT UMUM DAERAH PROVINSI NTB - Sulaimiah Sulaimiah; Santi Nururly; Joko Suprayetno; Mahyuddin Nasir (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2018)
This study aims to determine the significant relationship of individual characteristics, job characteristics, work environment either simultaneously or partially as well as dominant influence.This research is located in West Nusa Tenggara provincial hospital general administration section which consist of 60 people as respondent, research type used is associative research, data collecting method by questionnaire and interview and documentation with linear multiple regression analysis with f test and t test.The result of this research is significant influence of individual characteristic, work characteristic, work environment simultaneously influence to work stress, while partially individual characteristic and work environment have significant effect to work stress, while dominant influence is individual characteristic